Clinical and prognostic association of total atrial conduction time in patients with heart failure: a report from Studies Investigating Co-morbidities Aggravating Heart Failure. Issue 7 (July 2019) - Nuzzi, Vincenzo; Pellicori, Pierpaolo; Nikolaidou, Theodora; Kallvikbacka-Bennett, Anna; Torromeo, Concetta; Barilla', Francesco; Salekin, Damien; Kaur, Kuldeep; Monzo, Luca; Cleland, John G.F.; Clark, Andrew L.
Abstract : Background: The total atrial conduction time can be measured as the time from the onset of the P wave on the ECG to the peak of the A wave recorded at the mitral annulus using tissue Doppler imaging (A′; P-A′TDI); when prolonged, it might predict incident atrial fibrillation. Methods: We measured P-A′TDI in outpatients with heart failure and sinus rhythm enrolled in the SICA-HF programme. Results: P-A′TDI measured at the lateral mitral annulus was longer in patients with HF with reduced [LVEF<50%, N  = 141; 126 (112–146) ms; P  = 0.005] or preserved left ventricular ejection fraction [LVEF>50% and NT-proBNP > 125 ng/l, N  = 71; 128 (108–145) ms; P  = 0.026] compared to controls [ N  = 117; 120 (106–135) ms]. Increasing age, left atrial volume and PR interval were independently associated with prolonged P-A′TDI. During a median follow-up of 1251 (956–1602) days, 73 patients with heart failure died ( N  = 42) or developed atrial fibrillation ( N  = 31). In univariable analysis, P-A′TDI was associated with an increased risk of the composite outcome of death or atrial fibrillation, but only increasing log [NT-proBNP], age and more severe symptoms (NYHA III vs. I/II) were independently related to this outcome. Patients in whom both P-A′TDI and left atrial volume were above the median (127 ms and 64 ml, respectively) had the highest incidence of atrial fibrillation (hazard ratio 6.61, 95% CI 2.27–19.31; P  < 0.001 compared with those with both P-A′TDI and LA volume below the median). Conclusion: Measuring P-A′TDI interval identifies patients with chronic heart failure at higher risk of dying or developing atrial fibrillation during follow-up. Abstract : Supplemental Digital Content is available in the text